2000
DOI: 10.1128/jb.182.17.4979-4986.2000
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Stress Stimulons in Streptomyces coelicolor Revealed by Statistical Analyses of Global Gene Expression Patterns

Abstract: Stress-induced regulatory networks coordinated with a procaryotic developmental program were revealed by two-dimensional gel analyses of global gene expression. Four developmental stages were identified by their distinctive protein synthesis patterns using principal component analysis. Statistical analyses focused on five stress stimulons (induced by heat, cold, salt, ethanol, or antibiotic shock) and their synthesis during development. Unlike other bacteria, for which various stresses induce expression of sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
4
61
0
Order By: Relevance
“…1), as reported previously (Leskiw et al 1993;Puglia et al 1995;Vohradsky et al 2000). The antibiotics CDA and Red were first detected during T phase, whereas Act production was not detectable until S phase (Fig.…”
Section: Global Gene Expression During the Growth Of S Coelicolor M145supporting
confidence: 51%
“…1), as reported previously (Leskiw et al 1993;Puglia et al 1995;Vohradsky et al 2000). The antibiotics CDA and Red were first detected during T phase, whereas Act production was not detectable until S phase (Fig.…”
Section: Global Gene Expression During the Growth Of S Coelicolor M145supporting
confidence: 51%
“…S. coelicolor wild-type strain 1147 grew rapidly in YEME medium with a temporary (2 h) cessation of growth at the mid-exponential growth phase (Fig. 1a), possibly due to depletion of the nitrogen source, as previously pointed out by Vohradsky et al (2000). Later (at 42 h), cells entered into the stationary phase.…”
Section: K88e Mutants Show An Aberrant Growth Phenotypementioning
confidence: 50%
“…They suggested that this could be a linkage between carbon metabolism and stress response upon nutrient starvation. Thus, IIA Crr could be involved in controlling some of the many sigma factors that S. coelicolor possesses [4,41]. Further analyses are required to address the ideas mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…A specific interaction of IIA Crr with the maltose permease subunit MalK from Salmonella typhimurium was uncovered by surface plasmon resonance. These data suggest that this IIA Glucose -like protein may be involved in carbon metabolism in S. coelicolor.Keywords: inducer exclusion; protein phosphorylation; protein-protein interaction; Streptomyces; surface plasmon resonance.Streptomycetes undergo global changes in gene expression and enzyme activities in response to developmental stages, secondary metabolite production (antibiotics), carbon utilization, and stress conditions [1][2][3][4][5]. The focus of our research is the regulation of carbon source utilization (C-regulation) and how this influences the other abovementioned processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation